Marketing Strategy Of Bengkulu Latung Skin Craft At The Shop Bengkulu City Taste - Dedi Hermanto; Ahmad Soleh; Mimi Kurnia Nengsih (Journal of Indonesian Management, 2022)
The purpose of the study was to determine the marketing strategy of lantung leather craft at the Taste Shop of Bengkulu City in order to obtain maximum sales results. The samples in this study were internal samples (21 people) + external samples (30 people) = 51 people, namely customers from the Sari Rasa Store, Bengkulu City. The analytical method used is a SWOT analysis consisting of an Internal Strategy Factor Matrix (IFAS) and an External Strategic Factor Matrix (EFAS). Based on the results of research on the marketing strategy of latung leather handicrafts, Based on the results of the discussion presented based on the results of previous studies, it can be concluded that the results of the SWOT analysis show that the internal strategic factor analysis summary (IFAS) / strengths and weaknesses of 3.16 and external strategic factor analysis summary (EFAS)/opportunities and threats of the Taste Shop business with a total of 3.41 from these results, it is better for the Taste Shop business to use the SO strategy, namely by utilizing all business strengths in order to seize and take advantage of existing opportunities optimally.